Please solve this question ASAP.
The best answer will be marked brainliest.
The answer should be-
1) correct
2) well explained
3) Quick
Attachments:
![](https://hi-static.z-dn.net/files/d15/4c21167d42ae65793e7a5ec5d2435a2b.png)
Answers
Answered by
7
(x+ a) is factor of x^ +px+q
(-a)^+p(-a)+q=0
= a^-ap +q=0 (1)
(x+a) is a factor of x^ + mx + n
=(-a)^ +m(-a)+n=0(2)
From equation 1and 2
-ap-am +q -n =0
a(m-p)=n-p
a= n-p /m-p
Similar questions
Accountancy,
4 months ago
Physics,
4 months ago
History,
9 months ago
English,
9 months ago
Biology,
1 year ago